Planning benchmark study for stereotactic body radiation therapy of liver metastases: results of the DEGRO/DGMP working group on stereotactic radiation therapy and radiosurgery : physics contribution - Moustakis, Christos; Blanck, Oliver; Chan, Mark Ka Heng; Boda-Heggemann, Judit; Andratschke, Nicolaus; Duma, Marciana Nona; Albers, Dirk; Bäumer, Christian; Fehr, Roman; Körber, Stefan A.; Schmidhalter, Daniel; Alraun, Manfred; et al. (International journal of radiation oncology, biology, physics, 2022)
Purpose - Our purpose was to investigate whether liver stereotactic body radiation therapy treatment planning can be harmonized across different treatment planning systems, delivery techniques, and institutions by using a specific prescription method and to minimize the knowledge gap concerning intersystem and interuser differences. We provide best practice guidelines for all used techniques. - Methods and Materials - A multiparametric specification of target dose (gross target volume [GTV]D50%, GTVD0.1cc, GTVV90%, planning target volume [PTV]V70%) with a prescription dose of GTVD50% = 3 × 20 Gy and organ-at-risk (OAR) limits were distributed with computed tomography and structure sets from 3 patients with liver metastases. Thirty-five institutions provided 132 treatment plans using different irradiation techniques. These plans were first analyzed for target and OAR doses. Four different renormalization methods were performed (PTVDmin, PTVD98%, PTVD2%, PTVDmax). The resulting 660 treatments plans were evaluated regarding target doses to study the effect of dose renormalization to different prescription methods. A relative scoring system was used for comparisons. - Results - GTVD50% prescription can be performed in all systems. Treatment plan harmonization was overall successful, with standard deviations for Dmax, PTVD98%, GTVD98%, and PTVDmean of 1.6, 3.3, 1.9, and 1.5 Gy, respectively. Primary analysis showed 55 major deviations from clinical goals in 132 plans, whereas in only <20% of deviations GTV/PTV dose was traded for meeting OAR limits. GTVD50% prescription produced the smallest deviation from target planning objectives and between techniques, followed by the PTVDmax, PTVD98%, PTVD2%, and PTVDmin prescription. Deviations were significant for all combinations but for the PTVDmax prescription compared with GTVD50% and PTVD98%. Based on the various dose prescription methods, all systems significantly differed from each other, whereas GTVD50% and PTVD98% prescription showed the least difference between the systems. - Conclusions - This study showed the feasibility of harmonizing liver stereotactic body radiation therapy treatment plans across different treatment planning systems and delivery techniques when a sufficient set of clinical goals is given.